Autophagy, apoptosis, necroptosis, pyroptosis and netosis in pathogenesis of immune-inflammatory rheumatic diseases - M. Z. Saidov (Медицинская иммунология, 2022)
There are organized forms of cellular infiltrate observed in immune-inflammatory rheumatic diseases, i.e., ectopic follicle-like lymphoid structures and delayed-type response granulomas, whereas diffuse cellular inflammatory infiltrates represent non-organized forms. In these types of cellular infiltration, an integral pathogenetic link includes programmable cell death variants, with autophagy, apoptosis, necroptosis, pyroptosis and netosis being the most significant. There is a close relationship between these forms of cell death. This relationship occured in the process of biological evolution, being characterized by pronounced conservatism, and it follows general biological laws of molecular cellular processes. The “danger signals” (DAMPs) released during cell death induce a state of autoreactivity caused, e.g., by modulation of cell death processes using cellular PRR receptors of the innate immune system. When analyzing the processes of endocytosis, signaling pathways, adaptive molecules, transcription factors involved into these modes of cell death, we discuss pathogenetic role of changing membrane structures and molecular pathways of programmed cell death in immune-inflammatory rheumatic diseases. In this regard, there are fundamental membrane-associated cellular processes, genesis of various types of intracellular inflammasomes, cross-presentation of MHC-restricted products of disorganized loose fibrous connective tissue, and induction of innate and adaptive immune autoreactivity. Causal relationships of the molecular pathways for initiation of these forms of cell death, thus enabling identification of the molecular targets, in order to modulate productive inflammation.